Minnelide ameliorates Col4a5+/− mice by upregulating Col4a5 and alleviating endoplasmic reticulum stress - Ji, Bao-wei; Liu, Jun-chao; Wang, Xue; Yin, Ye; Zhang, Jing-jia; Wen, Fu-jie; Xu, Hong; Shen, Qian; Yu, Jian (Frontiers in Pharmacology, 2026)
BackgroundAlport syndrome (AS) is a progressive hereditary nephropathy caused by mutations in collagen IV genes, notably COL4A5, leading to proteinuria and kidney failure. Current therapies using RAAS inhibitors show limited efficacy. Triptolide, the main active component of Tripterygium wilfordii, exhibits anti-proteinuric effects but is limited by poor solubility and toxicity. Minnelide, its water-soluble prodrug, provides a promising alternative.ObjectiveThis study investigated the therapeutic potential and mechanisms of Minnelide in a female Col4a5 (X + X-) Alport syndrome mouse model.MethodsMice were treated with Minnelide or vehicle for 3 months. In vitro, Col4a5+/− podocytes were treated with triptolide, with or without Col4a5 siRNA knockdown.ResultsMinnelide significantly reduced proteinuria by 64.2%, improved glomerular pathology, upregulated renal Col4a5 expression, and suppressed endoplasmic reticulum (ER) stress. In podocytes, triptolide increased Col4a5 and alleviated ER stress. Col4a5 knockdown directly induced ER stress, which was reversed by triptolide treatment.ConclusionMinnelide demonstrates potent renoprotective effects in AS by upregulating Col4a5 expression and mitigating podocyte ER stress, positioning it as a novel therapeutic candidate.